Effect of an α‐Methyl Substituent on the Dienophile on Diels‐Alder endo:exo Selectivity. Issue 1 (15th January 2019) - Larrañaga, Olatz; de Cózar, Abel
Abstract: A detailed computational study of the Diels‐Alder reaction of cyclopentadiene with acrylonitrile, methylacrylate and their α‐methylated counterparts methacrylonitrile and methyl methacrylate at the M06‐2X(PCM)/TZVP level of theory has been performed. We want to understand the excellent exo ‐selectivities observed experimentally due the presence of this substituent. To this end, analysis of the reaction coordinate by means of activation strain model of chemical reactivity (ASM‐distortion interaction model) including solvation effects and NBO second order perturbation energy have been carried out. Abstract : What does methyl do ? Experimental evidence has shown that the presence of a methyl group in the dienophile drastically affects the endo : exo selectivity in Diels‐Alder cycloadditions. In this work, a detailed computational study including activation strain – distortion/interaction modelling and NBO second order perturbation energy calculations have been performed in order to shed light on the phenomenon.